Morphological, structural and optical properties of ZnO nanowires: The effect of growth time / Nurul Zulaikha Mohd Zamri ... [et al.] - Mohd Zamri, Nurul Zulaikha; Malek, Mohd Firdaus; Mohammad, Maryam; Bakri, Mohd Dzulfiqar; Rostan, Nur Fairuz; Khairul Azhar, Nurfatini Atiqrah; Mamat, Mohamad Hafiz; Shamsudin, Muhammad Salleh; Mahmood, Mohamad Rusop (Universiti Teknologi MARA Shah Alam, 2023)
Zinc oxide (ZnO) nanostructures (NSs) such as nanowires (NWs), nanorods, nanobelts, nanotubes, and nanonails have received a lot of attention in recent years due to their exceptional chemical and physical characteristics and wide range of potential uses. Researchers have investigated its possible uses in optoelectronic devices, field emitters, solar cells, sensors, and transparent electrodes due to its special features. This work is focused on a new method for the synthesis of ZnO NSs, particularly ZnO NWs, via microwave-assisted ultrasonic technique, with the advantages of low cost and the potential for large scale. The samples were evaluated with respect to the structural, morphological, and optical properties using various methods, such as field-emission scanning electron microscopy, X-ray diffraction, and UV-Vis spectroscopy. The reaction occurs in only 60 minutes with minimal energy expenditure. ZnO NWs produced at 600 W had diameters ranging between 33.53 and 41.81 nm and lengths that varied between 1.84 and 2.1 μm, were totally crystalline, and showed preferential growth in the (002) direction, which presented a hexagonal wurtzite structure.